Determinan Faktor Partisipasi Ibu Balita Dalam Kegiatan Posyandu di Desa Kejawan Putih Tambak Kecamatan Mulyorejo - Willianarti, Pipit Festy; Aryunani, Aryunani; Sumarliyah, Eni (Universitas Muhammadiyah Surabaya, 2017)
Implementation of neighborhood health center aims to reduce infant mortalityis accompanied by efforts to reduce the birth rate. For that selected priority programs such asmaternal and child welfare (MCH), family planning, nutrition improvement, immunization andprevention of diarrhea. IHC closely related with active community participation (participationmothers). Factors that influence the participation of mothers in the neighborhood health center activities include knowledge, attitude, affordability of health centers, social, economic, and health workers and cadres factors neighborhood health center.Methods this study uses an analytical methode with cross sectional approach. Total population 95 with a sample of 55 mothers, the samples were taken by simple random sampling. Data were collected by questionnaire and observation, then analyzed using statistical test Regrisi Binary Logistic with significance level of 0.05. The results showed that, the results of statistical tests Binary logistic regression showed knowledge factor (p = 0.000 <Î± = 0.05), showing the attitude factor (p = 0.002> Î± = 0.05) where health care affordability factor indicates (p = 0.003 <Î± = 0.05),and socioeconomic factors demonstrated (p = 0.010 <Î± = 0.05) and the factor of health workers and cadres posyandu (p = 0.355> Î± = 0.05). Based on these results it can be concluded that the knowledge factor, the affordability of the health service and social economy that affect the mother's participation in growth monitoring sessions.Â Â